Exogenous Factors Affecting Multifocal Electroretinogram: A mini review - Chen, Ai-Hong; Mohamad Rafiuddin , Muhamad Syukri; Coupland, Stuart (Scandinavian Journal of Optometry and Visual Science, 2021)
Multifocal electroretinogram (mfERG) is an important diagnostic tool in the clinical evaluation of central electro-retinal function of the macula. To enhance the diagnostic values and to improve its accuracy and internal consistency, it is crucial to examine carefully the endogenous and exogenous factors that affect mfERG recordings and clinical interpretations. This mini review focuses on three aspects of exogenous factors including (1) physiological variations pertaining to age and gender; (2) systemic changes owing to oxygen, blood pressure and glucose levels; (3) individual variables due to refractive status, pupil size, luminance and viewing condition.